Unveiling surfactant protein-A dynamics in human fetal lung development: histological and immunohistochemical insights from Myanmar - Saung A Kari; Zaw Myo Hein; Gehan El-Akabawy; Saung Yamone Naing (Folia Morphologica, 2025)
BACKGROUND: Surfactant protein-A (SP-A) is the most prevalent protein in the pulmonary surfactant system, and it is expressed in Type II alveolar epithelial cells. MATERIALS AND METHODS: We evaluated SP-A expression in 92 fetal human lungs at various gestational ages in Myanmar (Birma) using hematoxylin and eosin staining and immunohistochemical assays. RESULTS: We detected tubular structures in the fetal lungs during the canalicular stage of development at gestational weeks 22–25. Bronchioles were detected between 26–27 and 28–33 weeks, when primitive alveoli were evident. At 34–40 weeks, clusters of alveolar sacs opened from the alveolar ducts during the saccular development stage. At 40–44 weeks, extremely thin alveolar walls resembled sections of adult lungs. Type II cells secreting surfactant were undetectable at 22–25 weeks, but became detectable from 26 weeks, and the abundance of Type II cells increased after 28 weeks. Surfactant spread throughout the alveoli at 34 weeks. Because the positivity index of these cells significantly correlated with a gestational age of 26–33 weeks, we established a formula to estimate gestational age. CONCLUSIONS: Our findings improve understanding of fetal lung development and maturity, and provide valuable insights into the diagnosis and management of respiratory disorders among premature infants in Myanmar.